Sosialisasi Hasil Penelitian Potensi Ekowisata Minat Khusus di Kawasan Mangrove Kelurahan Sapat Kabupaten Indragiri Hilir - Arief Rachman B; Andi Yusapri; Syaiful Ramadhan Harahap; Faldi Gusti Indrawan; Muhammad Radi Ramadhan; Rizky Arya Ramadhan; Indra Wahyudi Tri Pangestu; Abdul Kadir; Ahmad Hafiz (CANANG: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aimed to enhance the understanding and participation of the residents of Sapat Village in developing the local ecotourism potential, including mangrove ecotourism, fishing, fireflies, sailing, beaches, and the socio-cultural heritage of fishermen’s communities. The program involved socialization, discussions, and the Focus Group Discussion (FGD) method to gain deeper insights into community perspectives and assess readiness for ecotourism development. Following the activities, an evaluation was conducted to assess participants' understanding before and after the program. The results showed a significant improvement, particularly in mangrove and firefly ecotourism, with an increase in the awareness of sustainable ecosystem management. However, the potential for beach ecotourism is less favorable due to environmental limitations, such as muddy substrates and tidal conditions. The community expressed strong support for technical assistance and training to develop ecotourism initiatives, especially mangrove and fishing activities, which are expected to boost local incomes and conservation efforts. This programme highlights the importance of continuous mentoring, capacity building, and monitoring to ensure the sustainability and economic impact of community-based ecotourism